Implementasi Metode SQ3R dalam Upaya Peningkatan Kemampuan Membaca Pemahaman Pada Mata Pelajaran Bahasa Indonesia Siswa SDN 135 Rejang Lebong - Mawaria Mawaria (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
This research is motivated by problems in learning Indonesian. The view of reading is difficult to be embedded in students. The learning process carried out does not provide opportunities for students to develop ideas in developing the potential of reading skills. Classroom Action Research (CAR) consists of 2 cycles, each of which consists of two meetings. The stages in each cycle consist of the stages of planning, implementation, observation or observation, and reflection. The research subjects were fifth grade students of SDN 135 RejangLebong consisting of 23 people in the 2016/2017 school year. In the first cycle student learning outcomes obtained an average of 73.19 and the percentage of classical learning completeness was 69.56%. In cycle II there were no more weaknesses that occurred in cycle I. Learning outcomes in the second cycle obtained an average of 81.69 with a percentage of classical learning completeness 91.30%. This fulfills the completeness criteria, ie 85% of students get a value of ,07.0 and the learning process is said to be completed individually if students get a value of ≥7.